Bio-economic production potentiality of Solanum lycopersicum under smart agroforestry practice - Md. Hafiz All Amin; Most. Akter; Arup Biswas; Md. Masud Rana Parvej; Sarkar Rayhan (Innovations in Agriculture, 2021)
Food security and maximum land use system are the priorities of crop production technique in the present global food growing environment. The tomato-Albizia lebbck agroforestry is an effective smart production approach. The aim of this research is to find out the appropriate combination of organic mulch leads the tomato Albizia lebbck agroforestry production as compared to sole cropping technique for growth, yield, and quality that brings health hygiene for fresh and cooked consumption. The experiment was laid out following two factors split plot design with three (3) replications. Tomato in open field (T0) and tomato under Albizia lebbeck woodlot agroforestry system (T1) were arranged in main plots. Conversely, the usage of organic mulches was set in sub-plots viz. M0= No mulch, M1= Ash mulch, M2= Saw dust mulch, and M3= Water hyacinth mulch. The results indicated the highest yield (32.65 t/ha) was found in water hyacinth mulch (M3) and the lowest yield (21.37 t/ha) was detected in M0 without mulch (control). The treatment M3 (water hyacinth mulch) gave the maximum sugar-acid ratio (12.04%) and minimum sugar-acid ratio (9.42%) was found in control (no mulch). Furthermore, the result showed the production potentiality was the highest yield (29.41 t ha-1) was found in tomato- Albizia lebbeck agroforestry (T1) and the lowest yield (25.95 t ha-1) was recorded in sole cropping of tomato (T0). The maximum sugar-acid ratio (11.37%) was found in tomato- Albizia lebbeck agroforestry (T1) and the minimum sugar-acid ratio (10.31%) was found in sole cropping of tomato (T0). On the other, the combined effect tomato- Albizia lebbeck agroforestry with water hyacinth mulch gave the highest yield (35.01 while, the lowest yield (22.47 t ha-1) was observed in sole cropping of tomato without mulch. The research finding also revealed the maximum benefit-cost ratio (4.94) was found from the tomato- Albizia lebbeck agroforestry which was 20 % higher than tomato was grown in sole cropping. Finally, the tomato- Albizia lebbeck agroforestry production in association with organic hyacinth mulch can be an effective production approach for maximum return in terms of yield, quality and money.